Rare case of deep pelvic retroperitoneal mature cystic teratoma - Valecha, Shalini Mahana; Ahmed, Maimoona; Oswal, Mona; Gandhewar, Manisha; Shende, Prajakta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Mature cystic retroperitoneal teratomas are typically rare childhood tumours. Less than 20% of these occur in adults more than 30 yrs of age. Our adult patient presented with such a tumour, which had grown to a disproportionately large extent. It was deeply embedded in the true pelvis extending laterally to the pelvic wall and inferiorly till the ischiorectal fossa and was adherent to the surrounding structures displacing all. A provisional diagnosis was made after MRI scan and patient was posted for exploratory laparotomy. After extensive blunt and sharp dissection, the cyst wall could be separated from the surrounding structures and successfully excised. Histopathology confirmed the diagnosis. Being such a rare tumour, it is essential to have a high degree of suspicion in such cases that can be supported by advanced imaging modality. Early diagnosis and complete surgical removal are the mainstay of management that provide an excellent prognosis for such patients.